The spatiotemporal differentiation and influencing factors of urban vitality in the border areas of China - Fengwei Ai; Qingshan Yang (PLoS ONE, 2025)
Based on the concept of urban vitality and the unique geographical location of border areas, an evaluation framework for urban vitality in border areas was constructed from four dimensions: economy, society, openness, and culture. The entropy weight method was used to calculate the urban vitality levels of 45 border cities in 2000, 2010, 2019, and 2022, and the influencing factors were quantitatively analyzed. The results indicated that from 2000–2022, the vitality level of China’s border cities continued to rise, from 1.38 to 6.57 with an average annual growth rate of 7.35%. The southwestern border region exhibited the highest growth rate, which was 5.3 times greater than that of the western border region with the slowest growth. Spatially, the areas with high urban vitality shifted from the northeast area to the southwest area, with key vitality centers emerging in Mudanjiang (northeast), Baotou (north), Bortala Mongolian Autonomous Prefecture (northwest), and Chongzuo (southwest). Among the influencing factors, openness vitality was found as the primary internal constraint on urban vitality, while border policies and innovation capabilities were identified as the most significant external drivers. This research aims to provide both theoretical insights and empirical evidence to guide the enhancement of border city vitality, contributing to the broader global discourse on border region development.